Potensi Hipertoleransi dan Serapan Logam Beberapa Jenis Tumbuhan pada Limbah Pengolahan Emas - Hidayati, Nuril; Saefudin, Saefudin (JURNAL BIOLOGI INDONESIA, 2005)
ABSTRACTPotency of Hypertolerance and Metal Absorption of Some Plant Species Under GoldMine Waste. Degraded mined land is characterized by extreme of alkalinity or acidity, highconcentration of soluble salt and high concentration of heavy metals. Contamination of minedsoil and water affects not only on agriculture system but also on food chains andepidemiological problems. As soil metal can not be biodegraded, remediation of soil heavymetal risk has been a difficult and expensive goal. Remediation of hazardous soil is requiredto reverse the risk to humans and the environment. Recently there are several differentstrategies available for the clean up and restoration of contaminat6d soils i.e conventionalwhich is mainly engineering-base and phytoremediation which is a biological-base method.Phytoremediation is defined as: clean up of pollutants mainly mediated by photosyntheticplants.. In this research four species of plants i.e Mimosa pigra, Crotalaria juncea, Crotalariasp. and lpomoea sp. were studied their potencies as hypertolerant plants on the waste of PTANEKA TAMBANG and public mines of Pongkor and Cigaru. The results showed that theplants were able to grow and showing high tolerance to the contaminated media. The mosttolerant species was lpomoea followed by Crotalaria and Mimosa. The results raised someprospectsfor phytoremediation technology for rehabilitating contaminated mined lands.Keywords: Phytoremediation, hypertolerance